Effect of Metal Concentration on Physicochemical Properties of Cobalt/Reduced Graphene Oxide Through One-Pot Greener Chemical-Thermal Reduction Using Ultrasonic Activation - Fatmawati, Dyah Ayu; Triyono, Triyono; Trisunaryanti, Wega; Chasanah, Uswatul (Rasayan Journal of Chemistry, c/o Dr. Pratima Sharma, 2022)
A combination of ultrasonically supported one-step chemical thermal reductions for synthesizing cobalt/reduced graphene oxide (Co/RGO) has been successfully carried out. This study aims to investigate the variation of Co concentration to GO (1, 5, and 10% w/w) on its physicochemical properties. GO precursor was prepared by the Tour method with an oxidizing agent:graphite weight ratio of 3.5. According to the findings of the investigation, in XRD spectra, the reduction treatment succeeded in shifting the diffraction peaks from 10° of GO to ~24° of Co/RGO. In FTIR spectra, the intensity of absorption peaks of O-H and C=O vibrations decreased after reduction. In SAA isotherm, Co-5/RGO material has the largest specific surface area of 109.753 m2/g with a pore volume of 0.158 cc/g and a pore diameter of 3.469 nm. Thus, this ratio (5% w/w) is the most optimal Co concentration that can be loaded to GO material.